USE OF NON-STANDARD LESSONS IN MATHEMATICS AT SCHOOL (World Bulletin of Social Sciences, 2023)
The article is devoted to using unconventional forms and methods of organization of lesson activities. Non-standard math lessons play an important role in the development of students, increasing their motivation to learn. The optimal combination of traditional and non-traditional lessons increases the effectiveness of the educational process. The article gives a General classification of non-standard lessons by the nature of the methods and methods used. Examples of organizing nonstandard math lessons in high school are given, as well as non-standard methods of knowledge control are described. Recommendations for choosing the form of organization of lessons depending on the set educational goals are offered